PENGARUH KOMITE AUDIT, PROPORSI KOMISARIS INDEPENDEN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Megasari Alfiyana, 14.05.52.0280; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2018)
This study aims to determine the effect of Audit Comitte, The Independent Commissioner, Profitability, and Size of Tax Avoidances. This study focused on manufacturing companies listedin Indonesia Stock Exchange (BEI) in the period 2014-2016 The sampling technique used was purposive sampling. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that the Audit Comitte, Profitability of significant negative effect on tax avoidances while variable Sizeof, The Independent Commissioner significant positive affect the tax avoidances.Keywords: Audit Comitte, The Independent Commissioner, Profitability, and Size of Tax Avoidance